Legal aspects of auxillary reproductive technologies in infertility treatment - V.Yu. Albitskiy; N.D. Odinayeva; V.O. Mansimova ("Paediatrician" Publishers LLC, 2011)
The article presents several aspects of legal regulation of auxillary reproductive technologies in treatment of infertility in Russia and other countries.Key words: auxillary reproductive technologies, method of extracorporeal fertilization, newborn, premature newborn, multiple pregnancy, embryo, infertility, law.